1997
DOI: 10.1124/mol.52.3.542
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of a Novel Thyromimetic on Lipoprotein Metabolism

Abstract: Although L-triiodothyronine (L-T3) lowers cholesterol, this hormone is not used to treat hypercholesterolemia because of its cardiotoxic effects. Thyromimetics, such as the novel compound CGS 23425, that mimic the beneficial but lack the detrimental effects of T3, may be useful in the treatment of hypercholesterolemia. To show that CGS 23425 has no cardiotoxicity, atrial contractility and force were both measured and found to be unchanged in rats treated with up to 10 mg/kg drug. The lipid lowering actions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 32 publications
0
56
0
Order By: Relevance
“…In 1963, the first of these thyroid hormone analogues was described (Blank et al 1963) and medicinal chemistry efforts since have demonstrated that selective thyromimetics can be produced through a variety of approaches. Specifically, liverselective, cardiac-sparing thyromimetics have been investigated as potential cholesterol-lowering drugs and their use for the prevention and reversal of atherosclerosis has been advocated (Taylor et al 1997, Chiellini et al 1998. Animal studies have shown promising results (Taylor et al 1997) and selective TR activation in rats and monkeys has been shown to provide a potentially useful treatment for obesity and cholesterol reduction (Grover et al 2004).…”
Section: The Use Of Tissue-selective Thyroid Hormone Analoguesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1963, the first of these thyroid hormone analogues was described (Blank et al 1963) and medicinal chemistry efforts since have demonstrated that selective thyromimetics can be produced through a variety of approaches. Specifically, liverselective, cardiac-sparing thyromimetics have been investigated as potential cholesterol-lowering drugs and their use for the prevention and reversal of atherosclerosis has been advocated (Taylor et al 1997, Chiellini et al 1998. Animal studies have shown promising results (Taylor et al 1997) and selective TR activation in rats and monkeys has been shown to provide a potentially useful treatment for obesity and cholesterol reduction (Grover et al 2004).…”
Section: The Use Of Tissue-selective Thyroid Hormone Analoguesmentioning
confidence: 99%
“…Specifically, liverselective, cardiac-sparing thyromimetics have been investigated as potential cholesterol-lowering drugs and their use for the prevention and reversal of atherosclerosis has been advocated (Taylor et al 1997, Chiellini et al 1998. Animal studies have shown promising results (Taylor et al 1997) and selective TR activation in rats and monkeys has been shown to provide a potentially useful treatment for obesity and cholesterol reduction (Grover et al 2004). However, the widespread use of these compounds for the treatment of metabolic disorders appears a long way off.…”
Section: The Use Of Tissue-selective Thyroid Hormone Analoguesmentioning
confidence: 99%
“…The results from these studies show the dual effects of thyroid hormone on apo AI gene activity. This information has already proven useful in the research and development of thyromimetics that may eventually prove to be useful in regulating levels of apo AI expression (Taylor et al 1997). …”
Section: Thyroid Hormonesmentioning
confidence: 99%
“…The two major subtypes of the thyroid hormone receptors that mediate these responses, TR␣ and TR␤, are the products of different genes and are also differentially processed to each yield two isoforms. It has been argued that modulation of heart rate and rhythm is mediated predominantly by activation of TR␣ 1 (2)(3)(4), and as a result, recent pharmaceutical research efforts have focused on developing specific TR␤ 1 agonists (5)(6)(7)(8).…”
mentioning
confidence: 99%